DESIGN OF STRUCTURE OF FLUID ARCHITECTURE CIBADAK, BANDUNG - Albert Riady, Irvan
Building construction projects require a good planning so the buildings that are built are safe and comfortable for its users. In Indonesia, design of structure must be planned as an earthquake resistant building, especially for the prone areas. For this reason, the design of structure will result a structural system that is different from general structure with structural elements that have higher requirements. Structure will be designed by dividing the structure into two parts, upper structure and lower structure. In the upper structure, it will be divided into building 1 and building 2 because there is a narrow link between that. The load applied in this structure refers to SNI 1727:2013 and ASCE 7-10. For the earthquake loads, specifically elaborated on SNI 1726:2012. To do structural modeling, initial dimensions and material specification are required. Structural modeling is done using ETABS software by considering the things that have been done before. Structural system in this building will be planned as a Special Moment Frame. The focus of structural analysis is earthquake resistant buildings with reference to SNI 1726:2012. Result of this check is the building that design had been safe from the earthquake load. Design of the structural elements refers to SNI 2847:2013 with the results of the type of beams are 24 pieces, columns 9 pieces, slabs 4 pieces, stairs 1 piece, ramp 1 piece, and all others checks already meet the requirements.